Extracorporeal Life Support in Multisystem Smooth Muscle Dysfunction Syndrome. (November 2017) - Prabhu, Sudesh; Fox, Scott; Mattke, Adrian; Armes, Jane E.; Alphonso, Nelson
We describe an infant with congenital mydriasis, patent ductus arteriosus (PDA), pulmonary hypertension, and cystic lung disease. She had all the major components of multisystemic smooth muscle dysfunction syndrome. Due to progressive respiratory deterioration, she required surgical PDA interruption, extracorporeal life support, and subsequent prolonged respiratory support. Genetic testing revealed ACTA2 R179H mutation and cystic lung disease on biopsy.